Treasure Island - Stevenson, Robert Louis (Leicestershire, UK : Ladybird Books Ltd, 1994)
Jim Hawkins sets off as cabin boy on the Hispaniola, to look for buried treasure.
Keywords: Folk Tales; Children stories